Siapkah pustakawan menghadapi eradigital ? - Jamridafrizal Jamridafrizal (Pusat Perpustakaan UIN Syarif Hidayatullah Jakarta, 2017)
Environment and technology will be constantly changing. The only certainty about the future is that it is significantly different from today. Librarians need to be discerning to read the signs of the profession so that they do not lead to the grave so they can not rise forever. What should be done by today's librarians to become ideal for their present user to bridge the expectation of future librarians to present users